Living Life as the Bachelor/ette: Contributions of Diverse Television Genres to Adolescents' Acceptance of Gendered Sexual Scripts. Issue 1 (2nd January 2022) - Ward, L. Monique; Grower, Petal; Reed, Lauren A.
ABSTRACT: Gendered sexual scripts (GSS) reflect stereotypes about the gender-specific behaviors expected in romantic and sexual relationships. Television may be a powerful contributor to these scripts for adolescents because of its stereotypical portrayals and prominence in their lives. However, although television use is a consistent predictor of adults' GSS, few studies have tested these relations among adolescents, especially U.S. adolescents, and most report null results. Across two studies, we sought to decipher these patterns, investigating whether U.S. adolescents' regular exposure to diverse TV genres predicted their acceptance of GSS. In Study 1, we surveyed 574 adolescents aged 13–18, testing whether their viewing of three TV genres (scripted programming, reality TV, music videos) was associated with their support of GSS, as measured by four scales. In study 2, we surveyed a national sample of 398 adolescents, testing whether their viewing of four TV genres was associated with their support of GSS. For both studies, viewing of reality TV was associated with stronger support of each measure of GSS; there were few contributions of other genres. Gender moderated one interaction in each study, demonstrating stronger contributions for girls. Implications are discussed for media literacy programs and for teen dating abuse.